Bilateral cystoid macular oedema and cotton wool spots associated with Henoch-Schonlein purpura. (9th August 2013) - Nicholson, Luke; Mathews, Divya
Abstract : We report a case of a male patient having bilateral cystoid macular oedema and cotton wool spots associated with Henoch-Schonlein purpura. He presented with decreased vision bilaterally measuring 0.2 (6/9.5) on the right and 0.5 (6/19) on the left. He has chronic hypertension with blood pressure averaging 150/90. His blood pressure was raised at 180/110 and with treatment reduced to 164/99. There were no other signs of malignant hypertensive retinopathy. He was treated with oral prednisolone and noticed a significant improvement the following day. An objective measurement performed 2 days later was −0.10 (6/4.8) bilaterally with resolution of macular oedema.